Hubungan Arcus Pedis Dengan Kelincahan Motorik Pada Anak Usia 3 - 4 Tahun - Firdiansyah, Ockta; , Agus Widodo, S.Fis., M.Fis (2016)
Background: Early childhood education is the most basic education and occupies a position as a golden age and very strategic in the development of human resources. Early childhood education is an effort aimed at the provision of early childhood which is done through educational stimulation to help the growth and further education. Age children is an age that only filled with playing and having fun. At this age they are more active than teens or adults. Few or many activities move would be one factor in a child's growth. One of the body's most important for the agility in children is arch of foot. Arch of foot is one of the foundation in a child's body agility. If the foundation is interrupted then disturbed also agility in children. Objective: The purpose of this study was determine the correlation of arch of foot against motor agility in children aged 3-4 years. Methods: This research was conducted using the analytic survey method with cross sectional approach. This research was conducted to study the dynamics of the correlation between risk factors with effects by collecting data at a time. Results: Research shows that a strong correlation between arch of foot against agility motor development of children aged 3-4 years with the value of the correlation coefficient 0,771 > 0,599. Conclusion: Arch of foot against motor agility in aged 3-4 years has a strong correlation. Keywords: Arch of foot, agility, zig-zag, children aged 3-4 years.